KNOWLEDGE-BASED EXPERT SYSTEM TO ASSIST PHYSICIAN FOR DIFFERENTIAL DIAGNOSIS OF CHOLERA TROPICAL DISEASES - Matumueni, Humberto Cuteso (International Journal of Engineering Science Technologies, 2025)
This article presents an expert system designed to assist physicians in the diagnosis of tropical cholera diseases, particularly those related to cholera. The objective of this article is to develop a framework for the diagnosis and monitoring of health care for cholera. The system is based on a set of rules and knowledge from doctors specializing in these pathologies. The design methodology is based on the collection of this knowledge to build a base of rules adapted to the specificity of symptoms and geographical contexts linked to tropical diseases. This system will potentially help doctors and the health sector to make a quick decision when diagnosing cholera. The development tool chosen for implementation is Exsys Corvid, a platform for creating and testing expert systems. Once the system is developed, its performance and effectiveness are validated using the K. Cohen method, which makes it possible to measure the reliability and agreement between the recommendations of the expert system and the diagnoses made by doctors. This system thus offers valuable support in the early detection of cholera diseases, reducing the risk of spread and optimizing the management of medical resources.